2020
DOI: 10.1101/2020.07.02.20141028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial Intelligence-Enabled, Fully Automated Detection of Cardiac Amyloidosis Using Electrocardiograms and Echocardiograms

Abstract: Although individually uncommon, rare diseases collectively affect over 350 million patients worldwide and are increasingly the target of therapeutic development efforts. Unfortunately, the pursuit and use of such therapies have been hindered by a common challenge: patients with specific rare diseases are difficult to identify, especially if the conditions resemble more prevalent disorders. Cardiac amyloidosis is one such rare disease, which is characterized by deposition of misfolded proteins within th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In the latest research, a human-interpretation-free machine learning pipeline based on the combination of ECG and echocardiography had been developed to detect cardiac amyloidosis. Multicenter study had confirmed that the artificial intelligenceenabled fully automated detection model outperformed interpretation by expert cardiologists in the diagnosis of cardiac amyloidosis [38]. On the other hand, speckle tracking imaging technology is widely used for the diagnosis of cardiomyopathy.…”
Section: Cardiomyopathymentioning
confidence: 95%
“…In the latest research, a human-interpretation-free machine learning pipeline based on the combination of ECG and echocardiography had been developed to detect cardiac amyloidosis. Multicenter study had confirmed that the artificial intelligenceenabled fully automated detection model outperformed interpretation by expert cardiologists in the diagnosis of cardiac amyloidosis [38]. On the other hand, speckle tracking imaging technology is widely used for the diagnosis of cardiomyopathy.…”
Section: Cardiomyopathymentioning
confidence: 95%
“…Thus, AI has the potential to evolve "expert intuition" into quantifiable science with the potential to improve the quality and accuracy of personalized medicine and individual-based clinical decision making. A few such examples converting "intuition" into more objective, quantitative approaches include: AI-enhanced electrocardiography (ECG) [4][5][6][7] ; ultrasonic echocardiography (UCG) 8,9) ; and serial bio-marker analyses 10) ; each of which provide patient-level quantitative CV disease risk prediction using multi-dimensional input data.…”
Section: The Potential Role Of High-performance Computing In Cardiovascular Sciencementioning
confidence: 99%
“…In the group using ECG AI, the detection rate of EF reduction increased by ∼30%. Goto et al developed an ECG AI for diagnosing cardiac amyloidosis [22] . In the model created using ECG data of 3191 cases, the performance was good, with the AUC of 0.91.…”
Section: Ecg Ai Researchmentioning
confidence: 99%